Convergent validity between a sport video game and real sport performance - Buns, M. T.; Thomas, K. T. (Sports Technology, 2011)
A challenge to expanding quality physical education programs is the expertise of teachers across many sports. In part this challenge exists because fewer experts are available to train pre-service teachers and coaches. Recent trends in instructional theory indicate that traditional forms of education represent only the tip of the iceberg regarding ways that individuals learn (VanDeventer questionnaire to identify participant basketball playing experience and videogame exposure; basketball knowledge test including tactical content, the AAHPERD Basketball Skill Test (1984) as an assessment of basketball shooting, passing, dribbling, and defensive skills, and three Basketball Video Gameplay sessions using a Nintendo Wii. The project was approved by the IRB, Human Subjects Review Committee. One-way ANOVA indicated that expert basketball players won significantly more video games than their novice counterparts [F (1,36) = 33.9, p < 0.001), E.S. = 0.50; expert M wins = 2.06, SD = 1.1, novice M wins = 0.44, SD = 0.51]. Basketball experience (expert or novice) was significantly related to videogame winning percentage (r = 0.65, p < 0.01) and average point differential (r = 0.63, p < 0.01). Basketball video game performance (wins/losses) was significantly related to basketball knowledge (r = 0.59, p < 0.01) and all four skills tests (shooting r = 0.72, p < 0.01, passing r = 0.67, p < 0.01, dribbling r = -0.56, p < 0.01, defense r = -0.62, p < 0.01). Multiple regression analysis indicated basketball experience group was a statistically significant predictor of video game performance (r = 0.544, p = .0012). The videogame was able to distinguish expert from novice basketball players on a number of performance outcomes including; total wins, average point differential, points, rebounds, steals, fouls, field goals, and free throws. Having more knowledge and skill in real world basketball translated to videogame performance, suggesting basketball videogames require similar tactical decisions of players as does real world basketball. Nintendo Wii basketball may be a viable learning tool for teachers or children with limited knowledge of basketball.